Effects of GeoGebra application on the performance of college students in Geometry - Rholey R. Picaza; Christie Jean V. Ganiera; Jerven Bregaño (Davao Research Journal)
In this quantitative research study, the impact of GeoGebra application as a pedagogical strategy on mathematics achievement in geometry was examined among 60 participants from two sections of students at Davao De Oro State College, Maragusan Branch. The experimental group, which received traditional teaching integrated with GeoGebra, demonstrated a significant improvement in trigonometry performance, with a mean gain score of 5.71, categorized as “Low.” In contrast, the control group, following a traditional approach, exhibited a more modest gain score of 1.56, categorized as “Very low.” A test of significant difference revealed no statistically significant disparities in pre-test scores between the two groups, emphasizing group equivalency before the GeoGebra intervention. The findings underscore the potential of GeoGebra application as an effective tool for enhancing trigonometry education and have implications for students, instructors, administrators, and future researchers in the field.